If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10n + -2 = 7n + 4 Reorder the terms: -2 + 10n = 7n + 4 Reorder the terms: -2 + 10n = 4 + 7n Solving -2 + 10n = 4 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. -2 + 10n + -7n = 4 + 7n + -7n Combine like terms: 10n + -7n = 3n -2 + 3n = 4 + 7n + -7n Combine like terms: 7n + -7n = 0 -2 + 3n = 4 + 0 -2 + 3n = 4 Add '2' to each side of the equation. -2 + 2 + 3n = 4 + 2 Combine like terms: -2 + 2 = 0 0 + 3n = 4 + 2 3n = 4 + 2 Combine like terms: 4 + 2 = 6 3n = 6 Divide each side by '3'. n = 2 Simplifying n = 2
| 2=-x-4 | | 5-7x-x=-27 | | (-10a^2b^5)(3a^4b)= | | 2x-4-6=-3 | | 7n-4=10n+14 | | xy+xz+yz=60 | | (a^10)(a^5)(a)= | | -60+10x=4x+18 | | 9n+6=8n+13 | | -12=2h+10 | | 4h-8h+11=39 | | -111-2x=99-9x | | 8-2q=12 | | x^2-4x+7=5x^2-3x-6 | | 18-2n=4n | | -2(3x+5)=7(4-x) | | 2n+27=5n | | log[2](5x-4)=4 | | 3x+3x=290-15 | | 6x-7=-3x+14 | | -x-50=-7+46 | | (4z+6)(9-z)=0 | | 15+4x=x+30 | | -27-7x=21-11x | | (1-y)(4y+5)=0 | | 2=18-4k | | 5x(2x-7)-12=5x(6x+3) | | 55-2x+3=4(x+6)+x | | 2y^2-7x-15=0 | | 11n+10=6n | | (-3x^4y^5)62= | | -54-5x=-9+22 |